2017
DOI: 10.1097/qad.0000000000001625
|View full text |Cite
|
Sign up to set email alerts
|

Perceived and posttraumatic stress is associated with decreased learning, memory, and fluency in HIV-infected women

Abstract: Design Multi-center, prospective cohort study Methods Every two years between 2009 and 2013 (3 times), 646 HIV+ and 300 demographically-similar HIV-uninfected (HIV-) women from the Women’s Interagency HIV Study completed neuropsychological (NP) testing and questionnaires measuring PRFs (perceived stress, post-traumatic stress disorder (PTSD) symptoms, depressive symptoms). Using mixed-effects regressions, we examined separate and interactive associations between HIV-serostatus and PRFs on performance over ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 45 publications
(56 reference statements)
0
38
0
Order By: Relevance
“…But the lack of studies with other groups lowered the generalisability and global relevance of their findings. Moreover, the meta-analysis was conducted in 2012, and the increase of publications about PTSD among PLWH since then24–26 suggests that a timely update is urgently needed. Indeed, several reviews provide a useful overview of the possible prevalence of PTSD among PLWH22 27; however, a number of gaps remain.…”
Section: Introductionmentioning
confidence: 99%
“…But the lack of studies with other groups lowered the generalisability and global relevance of their findings. Moreover, the meta-analysis was conducted in 2012, and the increase of publications about PTSD among PLWH since then24–26 suggests that a timely update is urgently needed. Indeed, several reviews provide a useful overview of the possible prevalence of PTSD among PLWH22 27; however, a number of gaps remain.…”
Section: Introductionmentioning
confidence: 99%
“…In the WIHS, current MDD via diagnostic interview was 20% and lifetime MDD was 32% versus 10% and 23% nationally 13 . In cognitive studies, about 30% of WIHS women report elevated depressive symptoms, [16][17][18] an estimate about 10% higher than other large-scale cohort studies of healthy midlife women [19][20][21] . Additionally, HIV+ women often have higher rates of depression 22 and more depressive symptoms than HIV+ men 7,[23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
“…Among HIV-uninfected (HIV-) individuals, depression severity is commonly associated with poorer episodic memory, executive function, psychomotor speed, and attention 27 . Across cross-sectional studies in PWH, the domains most reliably associated with depression are psychomotor speed (50% of studies), executive function (45%), learning and memory (42%), and motor function (44%) 28 followed by attention and working memory (38% 29 . In the MACS, depression is also associated with psychomotor speed (SDMT) and executive function (TMT-B minus TMT-A); however, other domains have not been examined 30 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding verbal fluency, five studies demonstrated an association with PTEs and SLEs (Malan-Muller Pukay-Martin et al, 2003;Rubin et al, 2017;Spies et al, 2016Spies et al, , 2017Watson et al, 2019). For attention/working memory, seven studies demonstrated an association with trauma (Clark et al, 2018;Kapetanovic et al, 2020;Lin et al, 2011;Pukay-Martin et al, 2003;Spies et al, 2016;Watson et al, 2019;Womersley et al, 2019); four studies demonstrated an association with processing speed, (Clark et al, 2012;Pukay-Martin et al, 2003;Spies et al, 2016; six studies demonstrated an association with learning (Rubin et al, 2017(Rubin et al, , 2015Spies et al, 2016Watson et al, 2019) while three studies demonstrated an association with motor function (Pukay-Martin et al, 2003;Spies et al, 2016;Womersley et al, 2019). Two studies (Deiss et al, 2019;Pukay-Martin et al, 2003) reported an association between global NCI and trauma (i.e.…”
Section: Cognitive Domainsmentioning
confidence: 98%